The Effect of Magnetic Iron Oxide Nanoparticles on Mice Liver and Kidney - A Nori; GH.R Amiri; B Taj; M Nasreesfahani; S Taj; A Valiyani (Journal of Kerman University of Medical Sciences, 2012)
Background & Aims: In spite of frequent produce and use of magnetic nanoparticles in biological fields, there are few studies on their side effects, especially under in-vivo conditions. Method: In this research, the effect of the single-dose intraperitoneal injection of DMSA (dimercaptosuccinic acid) coated magnetic iron oxide nanoparticles (Fe3O4) in different doses (50, 100, 200 and 300 mg/kg) on liver and kidney function was studied. Results: Clusters of iron oxide nanoparticles were observed in treatment mice liver and kidney tissues as dark blue accumulations with Prussian blue staining up to 4 days after administration; so, the nanoparticles were absorbed into and were accumulated in these organs. No histological disorders were observed in the tissue sections in comparison with controls. Considering biochemical analysis, the mean amounts of SGOT, SGPT, and LDH enzymes, also albumin, uric acid, urea and creatinine were not different significantly than control group; but in contrast to the control group, the mean numbers of the blood cells were decreased significantly in treatment groups with doses higher than 50 mg/kg. During the study, no death was found in animals. Conclusion: The data suggest that the future applications of DMSA- coated magnetic iron oxide in medicine and biology has not probably toxic effects on health human.